Diversity within the VP4 Gene of Rotavirus P[8] Strains: Implications for Reverse Transcription-PCR Genotyping - Iturriza-Gómara, Miren (American Society for Microbiology, 2000)
A degenerate version (1T1-D) of the rotavirus P[8]-specific primer (1T-1) allowed strains previously untypeable due to the accumulation of point mutations at the primer binding site to be P typed by reverse transcription-PCR. Sequencing of the cDNA followed by sequence alignment and phylogenetic analysis identified lineages and sublineages within the rotavirus P[8] types, while the use of 1T-1 or 1T-1D primers did not yield viral clusters in any particular lineage.